2004
DOI: 10.1002/rcm.1423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of common surfactants on protein digestion and matrix‐assisted laser desorption/ionization mass spectrometric analysis of the digested peptides using two‐layer sample preparation

Abstract: While surfactants are commonly used in preparing protein samples, their presence in a protein sample can potentially affect the enzymatic digestion process and the subsequent analysis of the resulting peptides by mass spectrometry. The extent of the tolerance of matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) to surfactant interference in peptide analysis is very much dependent on the matrix/sample preparation method. In this work the effects of four commonly used surfactants, namely n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 25 publications
2
70
0
Order By: Relevance
“…However, at very high concentrations (Ͼ1% wt/vol) of SDS the formation of crystals was difficult, it took longer for the samples to dry and excess sodium in the sample led to a deterioration of spectral quality. These trends are similar°to°those°reported°by°Zhang°and°Li° [29].…”
Section: Effect Of Sds On Peptide Mixturessupporting
confidence: 86%
See 2 more Smart Citations
“…However, at very high concentrations (Ͼ1% wt/vol) of SDS the formation of crystals was difficult, it took longer for the samples to dry and excess sodium in the sample led to a deterioration of spectral quality. These trends are similar°to°those°reported°by°Zhang°and°Li° [29].…”
Section: Effect Of Sds On Peptide Mixturessupporting
confidence: 86%
“…Similarly, BSA (66 kDa) digested in bicarbonate buffer resulted in an increase in sequence coverage from 28 to 45% when prepared with SDS near its CMC. While Zhang and Li have found that the presence of lower concentrations of SDS (Ͻ1%) does not affect tryptic digestion of proteins, they did not observe any trends relating to sequence coverage°as°a°function°of°SDS°concentration° [29].°We attribute the differences between these two findings to the sample preparation steps. SDS is added in the present study after tryptic digestion and the SDSpeptide mixture is vortexed thoroughly to ensure optimal peptide-micelle interactions.…”
Section: Effect Of Sds On Peptide Mixturesmentioning
confidence: 81%
See 1 more Smart Citation
“…The most common detergents are CHAPS and IGEPAL CA‐630. Detergents have to be removed before downstream LC‐MS analysis as they significantly influence peptide separation on the LC column53, 54 or interfere with ionization of analytes 55, 56. Therefore, thorough and repeated washing of IP samples is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we compared the efficiencies of urea, SDC, and OG for generating high yields of proteotypic peptides of 13 UGT isoforms in four biologic specimens. The efficiencies of proteolysis by trypsin in the presence of these denaturing agents are generally higher than those in the absence of the denaturant (Katayama et al, 2001(Katayama et al, , 2004Zhang and Li, 2004;Zhou et al, 2006;Chen et al, 2007;Masuda et al, 2008;Proc et al, 2010;Balogh et al, 2012). As done by others, the best practice would be investigating multiple peptides per protein when available (Harbourt et al, 2012;Ohtsuki et al, 2012;Schaefer et al, 2012;Fallon et al, 2013b;Achour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%